PROFIL KEPERCAYAAN DIRI PESERTA DIDIK SMP KELAS VIII - Nia Rahmat Jayadi; Wahyu Hidayat; Rima Irmayanti (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2023)
This study aims to examine and determine the self-confidence profile of students. This study uses descriptive quantitative methods. The subjects in this study were 35 students at level VIII at SMP Negeri 4 Pamulihan consisting of 2 classes, namely class VIII-A and class VIII-B. The data collection technique is through a self-confidence questionnaire. The results show the profile of students' self-confidence by class, namely with an average of 68.4 in the medium category for class VIII-A with a total of 20 students and an average of 77.9 in the medium category for class VIII-B with a number of participants. teach 15 students. According to gender, the average 69.9 is in the high category for boys with 14 students and the average is 74.2 in the medium category for women with 21 students. According to the aspect of self-confidence, namely the aspect of believing in one's own abilities with an average of 25.5 in the medium category, in the optimistic aspect with an average of 32.1 in the high category and on the responsible aspect with an average of 14.9 in the medium category. Judging from the difference in the average of each aspect, which has a low/medium average is the aspect of believing in one's own abilities and being responsible. This requires the right technique or method to improve these aspects so that it is better so that students' confidence can increase.